Occupational balance in parents of pre-school children: Potential differences between mothers and fathers - Sara Uthede; Ida Nilsson; Petra Wagman; Carita Håkansson; Lisette Farias (Scandinavian Journal of Occupational Therapy)
Background Parents of young children are a vulnerable group with an increased risk of stress-related health problems compared to adults without children. Low occupational balance has been identified as a risk factor for stress-related disorders.Aim The study aimed to describe occupational balance in parents of pre-school children and to explore potential differences between mothers and fathers.Method Data were collected by a web-based survey based on the Occupational Balance Questionnaire (OBQ11). A total of 302 working parents (200 mothers and 102 fathers) with at least one child under seven years of age were included in the study.Findings Mothers reported lower occupational balance than fathers with a median value of 10 for mothers and 12 for fathers (p = 0.029). Mothers rated significantly lower than fathers in three items; ‘Balance between work, home, family, leisure, rest and sleep’, ‘Having sufficient time for doing obligatory occupations’ and ‘Balance between doing things for others and for oneself’.Conclusion The results indicate that caring for pre-school children may negatively impact both parents, impacting mothers’ occupational balance to a greater degree.Significance Occupational therapists’ knowledge could be utilised to increase awareness of the importance of occupational balance within health services and improve mothers’ occupational balance.